2010
DOI: 10.1080/19768354.2010.525793
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diel abundance and feeding patterns ofChaoborus flavicansin Sang-Chun reservoir

Abstract: To document the basic ecological aspects of Chaoborus species, which has never been reported in Korea, we attempted to identify the species, to monitor seasonal and vertical dynamics, and to elucidate trophic relations of the species in Sang-Chun reservoir. Using morphological characteristics, we identified the collected samples as C. flavicans. Also, we compared the distribution of C. flavicans, Daphnia rosea and chlorophyll a to observed seasonal dynamics. The increase of C. flavicans was observed 1Á2 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The two older stages were reported to be on a higher trophic level than other zooplankton, as shown by stable isotopes of nitrogen (JEONG and PARK, 2010). In Lake Großer Vätersee the most important impact on the zooplankton community occurred when the larvae had reached the IVth instar which accounted for 90-95% of the yearly consumption.…”
Section: Predatory Impact Of Chaoborus On Zooplankton Community In Lamentioning
confidence: 98%
See 1 more Smart Citation
“…The two older stages were reported to be on a higher trophic level than other zooplankton, as shown by stable isotopes of nitrogen (JEONG and PARK, 2010). In Lake Großer Vätersee the most important impact on the zooplankton community occurred when the larvae had reached the IVth instar which accounted for 90-95% of the yearly consumption.…”
Section: Predatory Impact Of Chaoborus On Zooplankton Community In Lamentioning
confidence: 98%
“…Instars I and II fed primarily on phytoplankton, especially on Ceratium species. A stable isotope study of carbon showed these instars to be filter-feeders (JEONG and PARK, 2010). During the instar II stage, composition of the ingested food items slowly changed and started to include small zooplankton species (e.g., rotifers).…”
Section: Predatory Impact Of Chaoborus On Zooplankton Community In Lamentioning
confidence: 99%
“…Species in Chaoboridae have never known to inhabit Korea until recently, and even the family name did not appear in the Checklist of Insects from Korea (The Entomological Society of Korea and Korean Society of Applied Entomology, 1994). Recently, Jeong (2010) reported Chaoborus flavicans from the Sangchun reservoir in Gyeonggi-do, based mainly on mandible morphology and partial COI sequences. Therefore, their taxonomy and distribution are very poorly understood in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the traditional trophic level concept has limitations with regard to locating omnivorous species such as S. dehaani in food webs (Vander Zanden and Rasmussen 1996). Recently, stable isotopes and fatty acid biomarkers have become popular tools for studying food web structure (Jeong and Park 2010). Stable isotope monitoring can provide an objective and quantitative food web structure when ratios of stable isotopes such as carbon and nitrogen are measured from tissues of biological components in food webs (Vander Zanden et al 1999).…”
Section: Introductionmentioning
confidence: 99%